The International Student Experience at US Community Colleges at the Onset of the COVID-19 Pandemic - Whatley, Melissa; Fischer, Heidi (Journal of International Students, 2021)
This study’s purpose is to explore the impact of the COVID-19 pandemic on international students who were studying at U.S. community colleges at the onset of this public health crisis. While previous work has explored the impact of the pandemic on international students generally, we argue that community college international students deserve focused attention due to their potentially marginalized status on their campuses. Using a mixed methods research approach, we analyze survey and interview data provided by community college international educators. Our results speak to two overarching themes: the supports provided to students at the onset of the pandemic (and educators’ reasons for providing these specific supports) and the unique impact of the pandemic on community college international students due to their citizenship or residency status. These findings have important implications for community college leaders and international educators as they work with international students during future times of crisis.